Successful scaling of Edible City Solutions to promote food citizenship and sustainability in food system transitions - Plassnig, Sara Noemie; Pettit, Marisa; Reichborn-Kjennerud, Kristin; Säumel, Ina (Frontiers in Sustainable Cities, 2022)
Sustainable, productive and biodiversity-friendly urban landscapes are a strategic step in transitioning to future-proof, liveable and healthy cities for all citizens. Known as Edible City Solutions, these "edible nature-based solutions" comprise a wide range of different forms of urban food production, distribution and consumption which use innovative principles of ecological design combined with closed material and energy flows. These solutions reduce the overall ecological footprint of the city, enhance social cohesion, human health and wellbeing and contribute to bridging the gap between "farm and fork". Edible City Solutions are part of the local green economy, creating new and sustainable businesses and jobs. These benefits have been tested and monitored in Living Labs where a wide portfolio of different Edible City Solutions have been implemented and scaled in order to accelerate the uptake and use of (edible) nature-based solutions in urban landscapes. We document, discuss and analyse different scaling practices and activities from the Living Labs - together with local actors and within the "scaling community" (i.e. actors involved in each Living Lab and in the local Edible City community in Andernach, Berlin, Havanna, Oslo and Rotterdam, respectively). This process follows a mixed method approach. The study further offers an introduction to the co-created Living Labs, their ongoing scaling story and experiences and challenges as well as highlighting best practices. Scaling processes, strategies and approaches are critically reviewed and discussed. To sum up, observations are condensed into eleven golden rules of scaling (edible) nature-based solutions.